Entrapment of Rhizobium sp. by fluidized bed technique using polymers as coating materials - Rivera, Diego; Laboratorio de Microbiología de Suelos, Centro de Biotecnología y Bioindustria - CBB; Corporación Colombiana de Investigación Agropecuaria - Corpoica Km 14 Vía Mosquera - Bogotá D.C., Colombia. Universidad Nacional de Colombia-Facultad de Ciencias-Ciencias Farmacéuticas (2016)
The spray-drying technique was applied for the development of three solid formulations of Rhizobium. Sodium alginate and hydroxypropyl methylcellulose (HPMC) with concentrations of 0.5 % were used as polymers. Results showed that none of the solid formulations had negative effects in vitro on the growth-promoting capacities of Rhizobium sp. G58 (p < 0.05). PCA´s first three components explained 84.5 % of the total variance. This analysis concluded that the solid formulation had not negative effects on the biological nitrogen fixation activity in vitro or on the process of nodulation in greenhouse experiments. Symbiosis between Rhizobium and the plant was effective, which suggested that, under controlled conditions, the coating process with the polymers had allowed a controlled release of the bacteria and a proper transfer of Rhizobium sp. from the microparticles to the root of the plant.